Caterpillar bundles to win: operations strategy in action - Tayur, Sridhar (Henry Stewart Talks, 2012)
Product portfolio as strategic choice, Inventories growing faster than sales, Trade-off between market share and costs of complexity, Burning platform for radical change in operations strategy, Mathematical model for profit maximization, Customer behavior, Migration lists, Drivers of complexity, Bundling recommendation, Itemized value creation, Asymmetric strategy choice in duopolistic competition
Reviewed at 2017/12/31